An acetonic extract and secondary metabolites from the endolichenic fungus Nemania sp. EL006872 exhibit immune checkpoint inhibitory activity in lung cancer cell - SESAL, NÜZHET CENK (My University, 2022)
Copyright © 2022 Varlı, Pham, Kim, Taş, Gamage, Zhou, Pulat, Park, Sesal, Hur, Kang and Kim.Background: Endolichenic fungi (ELF), which live the inside the lichen thallus, contain many secondary metabolites that show various biological activities. Recent studies show that lichen and ELF secondary metabolites have antioxidant, antibacterial, antifungal, cytotoxic, and anticancer activities. Purpose: Here, the effects of an ELF extract and its bioactive compounds were investigated on the H1975 cell line focusing on immune checkpoint marker inhibition. Methods: An ELF was isolated from the host lichen Bryoria fuscescens (Gyelnik) Brodo and D. Hawksw and identified the species as Nemania sp. EL006872. The fungus was cultured on agar medium and acetonic extracts were obtained. Secondary metabolites radianspenes C and D, and dahliane D, were isolated from the crude extract. The biological effects of both the crude extract and the isolated secondary metabolites were evaluated in cell viability, qRT-PCR assays, flow cytometry analysis and western blotting. Results: The cell viability assay revealed that extracts from Nemania sp. EL006872 and the isolated secondary compounds had low cytotoxicity. The crude extract, radianspenes C and D, and dahliane D, suppressed expression of mRNA encoding PD-L1 and aromatic hydrocarbon receptor (AhR), and surface expression of PD-L1 protein by cells exposed to benzo[a] pyrene. Radianspenes C and D, and dahliane D, reduced expression of AhR, PD-L1, ICOSL, and GITRL proteins by H1975 lung cancer cells, as well as exerting anti-proliferative effects. Conclusion: Radianspenes C and D, and dahliane D, bioactive compounds isolated from Nemania sp. EL006872 ELF, have the potential for use as immunotherapy and immunoncology treatments.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; FARMAKOLOJİ VE ECZACILIK; Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; PHARMACOLOGY & PHARMACY; Farmakoloji; Farmakoloji (tıbbi); Pharmacology; Pharmacology (medical); benzo[a]pyrene; dahliane D; immune checkpoints; inducible T Cell costimulator ligand; Nemaniasp; programmed death-ligand 1; radianspenes C and D